Sustainable Water Management in Tidal Lowland Agriculture: A Research Agenda - Meitry Firdha Tafarini; Muhammad Yazid (Sriwijaya Journal of Environment, 2019)
Water in tidal lowlands may either lack or excessive.  Neither lack nor excessive of water is demanded for crop cultivation.  Therefore, water management plays an important role in the development of tidal lowland agriculture through maintaining proper water conditions.  Since tidal lowland with certain conditions is considered marginal, its utilization for crop cultivation should maintain its fragile characteristics such that its utilization to support crop production can be sustained.  Continuing use of tidal lowlands for crop production, therefore, requires agricultural ecosystem management through the establishment and measurement of sustainability in water management. Sustainable water management in tidal lowlands for crop production should not only consider the physical resources (infrastructures), but also human resource as well as financial resource.  This paper proposes three agendas for research on water management as follows: (1) identification of specific local water infrastructure developments, (2) initiation of  participatory operation and maintenance of water infrastructures, (3) utilization of self-supporting financial means in water management.